Is this a Public Law Case? - Butler, Andrew S (Victoria University of Wellington Law Review, 2000)
This article is a revised and updated version of a paper presented at the New Zealand Law Society Intensive on Public Law in September 1998. In it, Andrew Butler demonstrates the breadth of the concept of "public law" by investigating the application provision of the New Zealand Bill of Rights Act 1990 and the field of activity susceptible to public law judicial review. He concludes that nowadays a public law case can arise in settings (such as the formulation of common law private law, the interpretations of statutory private law, commercial contracts of public entities, regulatory acts of private bodies) far removed from those traditionally thought of as public law ones.